2015
DOI: 10.1039/c4ta04235b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of conjugated microporous polymer nanotubes with large surface areas as absorbents for iodine and CO2 uptake

Abstract: Conjugated microporous polymer nanotubes (CMPNs) were synthesized and employed as a platform for investigation of CO2 and I2 adsorption. A high adsorption capacity of up to 208 wt% for reversible I2 capture was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
147
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 215 publications
(155 citation statements)
references
References 52 publications
8
147
0
Order By: Relevance
“…The BCMP-1 and BCMP-2 were synthesized by Pb(II)/ Cu(I)-catalyzed Sonogashira-Hagihara cross-coupling polymerization from tetra(4-bromophenyl)methane and arylethynylene with different structures, which was proved as a reliable approach to construct CMPs networks [8,27]. The representative molecular structures for BCMP-1 and BCMP-2 are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BCMP-1 and BCMP-2 were synthesized by Pb(II)/ Cu(I)-catalyzed Sonogashira-Hagihara cross-coupling polymerization from tetra(4-bromophenyl)methane and arylethynylene with different structures, which was proved as a reliable approach to construct CMPs networks [8,27]. The representative molecular structures for BCMP-1 and BCMP-2 are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, a variety of CMPs with different morphologies and functionalities have been designed and synthesized as porous mediums for various purposes including hydrogen storage [23,24], CO 2 capture [25][26][27], iodine capture [27], composites [28], and oil absorption [22,[29][30][31]. In particular, we firstly reported the superhydrophobic and superoleophilic wettabilities of the CMPs [22].…”
Section: Introductionmentioning
confidence: 99%
“…Sigen et al reported a metalloporphyrin-based conjugated microporous polymer (CMP) with exceptional performance in the reversible adsorption of iodine [2]. In our previous work, we prepared CMP nanotubes as absorbents with an excellent uptake of 208 wt% for iodine capture, which is one of the highest values reported for porous materials [13]. However, in most cases, some disadvantages for these solid adsorbents are related to high-cost production and complicated fabrication process as well as the uncertain Electronic supplementary material The online version of this article (doi:10.1007/s10853-015-9289-1) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 96%
“…CMPs, a class of amorphous materials possessing three-dimensional networks with their building blocks linked in a p-conjugated fashion, have emerged as an important material platform since 2007. 27 Later on, they are extensively utilized in gas adsorption, [28][29][30][31] electrical energy storage, [32][33][34] and especially in chemosensors [35][36][37] owning to their high sensitivity and technical simplicity. However, the difficulty in processing and device integration have been considered as the Achilles heel for CMPs to be competitive in future applications.…”
Section: 15mentioning
confidence: 99%